41) What should be taken away from 3x2 - 4y2 + 5xy + 20 to obtain – x2 - y2 +
6xy + 20
Answers
Answered by
3
Answer:
Hope it helps!! Mark this answer as brainliest if u found it useful and follow me for quick and accurate answers...
Step-by-step explanation:
Let q should be subtracted.
Then according to question,
3x^2 – 4y^2 + 5xy + 20 - q = -x^2 – y^2 +6xy + 20
⇒ q = 3x^2 – 4y^2 + 5xy + 20 - ( - x^2 - y^2 + 6xy + 20)
⇒ q=3x^2 – 4y^2 + 5xy + 20+ x^2 + y^2 – 6xy – 20
⇒ q = 3x^2 + x^2 – 4y^2 + y^2 + 5xy - 6xy + 20 – 20
⇒ q = 4x^2 – 3y^2 – xy + 0
Hence, 4x^2 – 3y^2 - xy should be subtracted.
Similar questions